Pre-service teachers’ use of educational applications during work-integrated learning in south African primary schools - Mogale, Makobo; Jita, Thuthukile (Edelweiss Applied Science and Technology, 2025)
Mobile technology has evolved and become accessible to classroom learning. Responding to digitalization in higher education institutions, using educational applications has become inevitable and crucial to prepare students for a dynamic world in which technology takes center stage. The 2015 university disruptions caused by the #FeesMustFall protests and the recent outbreak of Covid-19 shed light on the need to strengthen technological educational systems. This paper uses the Technology Acceptance Model as a theoretical lens to explore pre-service teachers’ use of educational apps during their teaching practicum, referred to as work-integrated learning (WIL). The study is placed within an interpretive paradigm and is qualitative in nature. Data were collected through interviews with nine pre-service teachers doing WIL in three primary schools and analyzed thematically. The study makes a significant contribution to the scholarship of digital transformation in teacher education programs. Furthermore, it ascertains the possibilities and challenges of increased digital transformation affordances in teaching–learning strategies and pre-service teachers’ classroom practices during WIL.